Antimicrobial resistance to disinfectants in biofilms - Paula Araújo (2011)
Microorganisms have a natural capacity to attach to surfaces, to multiply and to embed themselves in a slimy matrix, forming biofilms. These allow complex interactions among different species and surfaces. There is significant evidence that bacterial growth in attached communities constituted the first form of life on the planet, and it is estimated that the majority of microbial activity on earth is resultant from biofilms, rather than microbes growing isolated in the form of planktonic cells. Industrial units, particularly food processing plants, provide good environmental conditions for biofilm proliferation, such as an abundant source of nutrients, which can create a significant problem mainly because most of these microorganisms can be pathogens. Therefore, cleaning and disinfection in food processing plants are important issues that deserve full consideration. However, the phenotype of biofilms provides intrinsic resistance to cleaning and disinfection. Nowadays, there are no biofilm control strategies that inactivate, remove or prevent their regrowth after antimicrobial treatment.This study provides information on the problems of biofilm formation and on the main strategies used for their control. Information on the antimicrobial mode of action of biocides and biofilm resistance mechanisms is also provided.